Repositorio de material audiovisual como recurso didáctico para la enseñanza en la educación general básica, en la Carrera de Educación Básica de la Facultad de Ciencias de la Educación Humanas y Tecnologías de la Universidad Nacional de Chimborazo. Periodo 2023-2024. - Freire Salazar, Katherine Lizeth (2024)
The following research work aims to present a repository of audiovisual material, of audiovisual resources for teaching in basic general education, with audiovisual productions that were created for presentation in the different editions of the festival "Wayra Taki". Its development aims to contribute to the implementation of this didactic resource as part of the teaching-learning process. The approach of this research project is mixed; quantitative because data are analyzed through a tabulation with tables and graphs; qualitative because the problem was observed, described, and collects genuine ideas of the population studied. As a result of this project, it is concluded that, although teachers confirm the importance of the use of audiovisual materials as a didactic resource, they do not know the different genres and formats that exist, besides they do not consider that the audiovisuals produced within the Faculty of Educational Sciences, Humanities and Technologies, are useful as a didactic resource for their classes. The repository presented has been created with the intention of uploading on this platform the audiovisuals of educational interest created in the Faculty, being selected and classified according to their communicative intention, each one has a technical data sheet, where relevant data about the video and its authorship are detailed to safeguard the integrity of the authors. We can find it under the name "Educación Básica Wayra Taki Unach", the divided page is divided into sections: Literary, Musical, Miscellaneous, Promotional, Documentaries, Tutorials, Docudrama. This channel has a free access to the general public for its use.